Pharmacokinetic-pharmacodynamic relationships of immunoglobulin therapy for envenomation. - Gutiérrez, José María (2003)
Parenteral administration of horse- and sheep-derived antivenoms constitutes the cornerstone in the therapy of envenomations induced by animal bites and stings. Depending on the type of neutralising molecule, antivenoms are made of: (i) whole IgG molecules (150 kDa), (ii) F(ab')(2) immunoglobulin fragments (100 kDa) or (iii) Fab immunoglobulin fragments (50 kDa). Because of their variable molecular mass, these three types of antivenoms have different pharmacokinetic profiles. Fab fragments have the largest volume of distribution and readily reach extravascular compartments. They are catabolised mainly by the kidney, having a more rapid clearance than F(ab')(2) fragments and IgG. On the other hand, IgG molecules have a lower volume of distribution and a longer elimination half-life, showing the highest cycling through the interstitial spaces in the body. IgG elimination occurs mainly by extrarenal mechanisms. F(ab')(2) fragments display a pharmacokinetic profile intermediate between those of Fab fragments and IgG molecules. Such diverse pharmacokinetic properties have implications for the pharmacodynamics of these immunobiologicals, since a pronounced mismatch has been described between the pharmacokinetics of venoms and antivenoms. Some venoms, such as those of scorpions and elapid snakes, are rich in low-molecular-mass neurotoxins of high diffusibility and large volume of distribution that reach their tissue targets rapidly after injection. In contrast, venoms rich in high-molecular-mass toxins, such as those of viperid snakes, have a pharmacokinetic profile characterised by a rapid initial absorption followed by a slow absorption process from the site of venom injection. Such delayed absorption has been linked with recurrence of envenomation when antibody levels in blood decrease. This heterogeneity in pharmacokinetics and mechanism of action of venom components requires a detailed analysis of each venom-antivenom system in order to determine the most appropriate type of neutralising molecule for each particular venom. Besides having a high affinity for toxicologically relevant venom components, an ideal antivenom should possess a volume of distribution as similar as possible to that of the toxins being neutralised. Moreover, high levels of neutralising antibodies should remain in blood for a relatively prolonged time to assure neutralisation of toxins reaching the bloodstream later in the course of envenomation, and to promote redistribution of toxins from extravascular compartments to blood. Additional studies are required on different venoms and antivenoms in order to further understand the pharmacokinetic-pharmacodynamic relationships of antibodies and their fragments and to optimise the immunotherapy of envenomations.